A Virtual "Think Tank" to Establish Collaborative Leadership Initiative Plans ("CLIPs") - Whitney D. Maxwell; Kerry K. Fierke; Gregory M. Zumach (University of Minnesota Libraries Publishing, 2022)
The AACP Leadership Development Special Interest Group (LD SIG) held a one-hour Virtual Networking Session during the American Association of Colleges of Pharmacy (AACP) 2020 Annual Meeting. The purpose of the session was to connect attendees with colleagues from other institutions sharing similar interests related to leadership development through an engaging "Virtual Think Tank" (VTT). The VTT included facilitated collaboration which enabled small groups to develop "Collaborative Leadership Initiative Plans" (CLIPs) based on shared leadership interest areas.  A CLIP is an idea for a multi-institutional programmatic or scholarly initiative that is expected to lead to deliverables or outcomes mutually beneficial for all collaborators.  Facilitators then assisted the CLIP groups with identifying specific deliverables and potential outcomes of successful implementation, as well as a plan for group follow-up. Seventy-two attendees from 55 unique institutions participated to form seven CLIP groups consisting of an average of ten individuals each. CLIP ideas generated included an initiative to align faculty tenure and promotion criteria to incentivize entrepreneurship and innovation among faculty, incorporation of a leadership project into Advanced Pharmacy Practice Experiences in the experiential pharmacy curriculum, and creation of a cross-institutional co-curricular program for students.  An important legacy of the session was a leadership networking contact list, called the Leadership Networking Database, which will serve as an enduring leadership networking tool.  This session offered an innovative solution to a canceled in-person professional meeting and replaced missed networking and collaboration opportunities resulting from cancellation of the in-person meeting.